Two-Stage Performance Evaluation of Domestic and Foreign Banks in Taiwan - Chiu, Sheng-Hsiung; Lin, Tzu-Yu (Asian Journal of Economic Modelling, 2018)
This paper provides an integration of independent component analysis and network slacks-based measure for performance analysis for foreign and domestic banks in Taiwan Independent component analysis was used to reduce data dimensionality of variables for a more discerning data envelopment analysis (DEA) performance evaluation. The authors then adopted performance evaluation structure based on a two-stage network model using network slacks-based measure: the production efficiency and the profitability efficiency. This study showed that domestic banks were more efficient than foreign banks in operational performance and production efficiency. The empirical results of the proposed ICA-NSBM model may be used to improve the discriminative ability of the performance evaluation using DEA methodology.